Book Review: Asian Data Privacy Laws: Trade and Human Rights Perspectives - Rosadi, Sinta Dewi (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2015)
This book is written by Professor Graham Greenleaf, an expert in the field of privacy law from Faculty of Law, University of New South Wales, Sydney, Australia. This book compiles his research and advocacy in Asias privacy development since 1970, as well as his writings on Asian Privacy Development in Privacy Laws & Business International Report. This book is the result of his long collaboration with many privacy law experts from many States in Asia and has been published in numerous books and journals. The book is written because the author believes that privacy in its many forms is worth protecting as one of the rights protected under human rights laws. The author also believes that personal data has a high economic value, which leads to the book also examining the business aspects of the data privacy laws and the extent to which corporations take part in data privacy protection.Â DOI: https://doi.org/10.22304/pjih.v2n2.a11